Optimisation of octahedral metal complexes through spin-crossover modulation for harversting thermoelectrochemical energy / Megat Muhammad Ikhsan Megat Hasnan - Megat Muhammad Ikhsan, Megat Hasnan (2019)
Thermo-electrochemical cell (TEC) technology allows the conversion of a thermal gradient into electricity due to the Seebeck effect using inert electrodes and active redox electrolyte. TEC require a high entropy difference for high power density. This study proposes the use of a family of spin crossover (SCO) metal complexes as the TEC material. The change of spin states from high spin (HS) to low spin (LS) or vice versa, is utilized as the key mechanism in enhancing the entropy difference, and hence Seebeck coefficient of the system. The scope of this study is divided into three: (1) molecular modeling of the SCO complexes, (2) SCO composite optimisation and (3) proposing micro-TEC device design and fabrication process for future work. The SCO materials used in this work are based on an octahedral structure of transition metals (Iron, Cobalt and Manganese). Density Functional Theory (DFT) is used to correlate between molecular conformation and electrochemical HOMO-LUMO gap that provides a fundamental understanding of the SCO molecule as a function of its spin states. The SCO complexes synthesised is analysed using electrochemical impedance spectroscopy and cyclic voltammetry to provide a comprehensive picture of the thermoelectric performance of these SCO composite. The lower electrochemical HOMO-LUMO gap energy of a high in stable LS Fe in MPN obtained from molecular modeling and CV analysis explained the basis high ionic conductivity of Fe in MPN by three orders magnitude higher compared to Fe, Mn and Co in DMSO. Interestingly, the agglomeration of the Fe complex in MPN, in the form of spherical micelles (diameter ~200 nm,) provided an explanation its high Seebeck coefficient, as the high entropy of such an agglomeration resulted in a high Seebeck coefficient. The optimised micelle stability of Fe complex through 1% wt of PMMA additive to form gel TEC material shows power output of one order of magnitude higher (60μWm-2 at ΔT=60°C) than power output of the conventional KI-KI3 redox couple and complexes in solution (3-5 μWm-2). As a final study, module of TEC generators was fabricated using MEMS technology to provide a realistic platform for waste heat energy harvesting. Then, this work provide a systematic study of optimization of SCO metal complexes for energy harvesting from fundamental molecular design to SCO material synthesis and analysis to device fabrication. The gel Fe complex was the best SCO material compared to Mn and Co due to high SCO molecular stability and stable micelles formation capability thus enhance TEC performance through enhancement of both Seebeck coefficient and conductivity simultaneously.